Urbanisation And The Challenges Of Building Sustainable Cities - Bhurtun, Poonam; Shukri, Sharyzee Mohmad; Abdullah, Azli; Sahabuddin, Mohd Firrdhaus Mohd (MAJ - Malaysia Architectural Journal, 2024)
Urbanisation And The Challenges Of Building Sustainable Cities